Mekanisme Penetapan Daftar Pemilih dalam Perspektif Hukum - Zairudin, Ahmad (Legal Studies Journal, 2021)
The implementation of the General Elections (General Elections) is generally regulated in Article 22E of the 1945 Constitution. Elections are a benchmark for dignified democratization and as a means of channeling human rights of citizens who are very principled. The right to vote as a human right is an important part of the principle of popular sovereignty which is reflected in the principles of democracy and becomes the main foundation in the state as outlined in the constitution. The main objective of laying people's sovereignty is the appreciation and assessment of the right of the people to choose and determine the direction of the life of the state with the aim of ensuring shared prosperity. Determination of voters (DPT) carried out by the General Election Commission (KPU) is part of a series of electoral systems which have an important position in the implementation of elections. Where the authority of the KPU above is emphasized in the Act No. 7 of 2017 Election Law. Keywords:  General Elections, People, Democracy, and Permanent Voters List